2017
DOI: 10.1002/anie.201611843
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Thermodynamic Signatures of an RNA Thermometer by Osmolytes and Salts

Abstract: Folding of ribonucleic acids (RNAs) is driven by several factors, such as base pairing and stacking, chain entropy, and ion-mediated electrostatics, which have been studied in great detail. However, the power of background molecules in the cellular milieu is often neglected. Herein, we study the effect of common osmolytes on the folding equilibrium of a hairpin-structured RNA and, using pressure perturbation, provide novel thermodynamic and volumetric insights into the modulation mechanism. The presence of TMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…Studies have shown that tertiary interactions lead to as ubstantial decrease in the phosphatesS ASA, thereby stabilizing the folded state of the RNAi nt he presence of TMAO. [17] In agreement with these data, we found that TMAOp redominantly assists population of the folded state of the DNAH p ( Figure 1a nd Figure S2), because also for such DNAH ps tructure the unfolded conformation has al arger SASA of exposed phosphate and nucleobase groups than the folded conformation. [13] The interaction between TMAOand nucleobases is also energetically unfavorable and therefore provides anet stabilization of the DNAd uplex structure based on nucleobase SASA.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Studies have shown that tertiary interactions lead to as ubstantial decrease in the phosphatesS ASA, thereby stabilizing the folded state of the RNAi nt he presence of TMAO. [17] In agreement with these data, we found that TMAOp redominantly assists population of the folded state of the DNAH p ( Figure 1a nd Figure S2), because also for such DNAH ps tructure the unfolded conformation has al arger SASA of exposed phosphate and nucleobase groups than the folded conformation. [13] The interaction between TMAOand nucleobases is also energetically unfavorable and therefore provides anet stabilization of the DNAd uplex structure based on nucleobase SASA.…”
supporting
confidence: 85%
“…[13] TMAOi nteracts unfavorably with the phosphate backbone and nucleobases of the nucleic acids structure,and therefore exclusion of TMAOfrom these surfaces is exothermic and entropically costly. [17] Forc anonical double-stranded DNAs tructures,p ressure has been shown to have either astabilizing,destabilizing or no effect on the structure of the DNA, depending on the temperature and salt concentration. Urea interacts strongly with nucleobases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact values depend the change in SASA of the protein upon unfolding. Slightly lower values have been found for RNA secondary and tertiary structures . Both, the transfer model and the preferential interaction coefficient can be related to the m ‐value, that is, m=iniαiδgitr=-RTΔΓBC/cnormalC .…”
Section: Cosolvent Effects On the Folding Equilibrium Of Proteins Anmentioning
confidence: 99%
“…Living cells respond to physical and chemical stresses like temperature, pressure, pH, salinity, and desiccation with changes in the pattern of gene expression . As a response to such stressors, the structure and dynamics of biomolecules may also be altered . Recently, it has been found that noncanonical DNA structures, such as G‐quadruplexes (G4‐DNAs) formed by guanine‐rich nucleic acid sequences, are markedly responsive to such stimuli .…”
Section: Figurementioning
confidence: 99%